MENINGKATKAN SEMANGAT BELAJAR PADA ANAK-ANAK DAN MEMBANTU MASYARAKAT DALAM KEGIATAN BERTANI DI DESA MBINANGA - Riau Wanshi Manik; Gokma Nababan; Ivan Gultom; Welmar Olfan Basten Barat (Abdi Jurnal Publikasi, 2023)
Pegagan Hilir is a sub-district in Dairi Regency, North Sumatra Province, Indonesia. Pegagan Hilir District is 24 km away from the capital of Dairi Regency, Sidikalang. Community Service activities are carried out with activities which are generally divided into two activities in the educational sector by providing afternoon tutoring and in the social sector by conducting interviews and assisting the activities of farmers in Mbinaga Village. Things that were successful during the service: the weekly attendance of the children showed that the children's enthusiasm and enthusiasm increased every week. They also showed increased concern and solidarity with each other. based on interviews conducted by many people who complained about the lack of funds to run their farms. so there is a need to support farmer groups by providing strength through increasing access to aid and capital facilities through 2 areas, namely education and social a. The children in Mbinanga village have high enthusiasm and enthusiasm for education. This is very good for supporting progress in the field of education for future generations by instilling the values ​​of caring and cooperation to achieve common goals. B. Farmers in Mbinanga village need to get support from farmer groups to improve farmer welfare with the help of improving facilities and capital.